Case report: cryptococcal meningitis in an apparently immunocompetent patient in Nepal - challenges in diagnosis and treatment - Jha, A; Adhikari, S; Sigdel, K; Paudyal, B; Basnyat, B; Kayastha, G; Pradhan, S; Risal, U; Poudel, J (F1000 Research, 2019)
A 50 year old woman from Nepal had clinical features suggestive of meningitis. Cerebrospinal fluid (CSF) analysis was normal except for the presence of cryptococcal antigen. The inclusion of test for Cryptococcus in the CSF helped in making the diagnosis of cryptococcal meningitis in our patient who was apparently immunocompetent. Treatment with liposomal amphotericin B could not be started on time due to financial constraints. The patient had a stroke and further deteriorated. Liposomal amphotericin B is stocked by the government of Nepal for free supply to patients with visceral leishmaniasis, but the policy does not allow the drug to be dispensed for other infections. The family members of our patient acquired the drug within a few days from a government center using their political connections and following administering the treatment the patient improved. This case demonstrates the utility of considering cryptococcal meningitis as a differential diagnosis, and including tests for Cryptococcus when dealing with immunocompetent patients presenting with meningitis. It also demonstrates the effects of the sociopolitical situation on health care delivery in low- and middle-income countries (LMICs) such as Nepal.